Facile reduction of aromatic nitro compounds to aromatic amines catalysed by support-free nanoporous silver1. Issue 38 (30th April 2015) - Li, Zhiwen; Xu, Xiaohong; Jiang, Xiaojian; Li, Yingchun; Yu, Zhixin; Zhang, Xiaomei
<x xml:space="preserve">Abstract</x> Reduction of aromatic nitro compounds to aromatic amines was realized in excellent yields by using nanoporous silver as a sustainable, heterogeneous catalyst.